2011
DOI: 10.1007/s00122-011-1606-8
|View full text |Cite
|
Sign up to set email alerts
|

QTL identification of flowering time at three different latitudes reveals homeologous genomic regions that control flowering in soybean

Abstract: Since the genetic control of flowering time is very important in photoperiod-sensitive soybean (Glycine max (L.) Merr.), genes affecting flowering under different environment conditions have been identified and described. The objectives were to identify quantitative trait loci (QTLs) for flowering time in different latitudinal and climatic regions, and to understand how chromosomal rearrangement and genome organization contribute to flowering time in soybean. Recombinant inbred lines from a cross between late-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
1
21
0
7
Order By: Relevance
“…Two of the SSR markers amplifying unique alleles were known to be linked with two different phenotypic traits. The Satt055 was reported to be linked with photoinsensitivity trait (Liu et al 2011). The Satt055 had amplified a unique allele in accessions EC333915.…”
Section: Molecular Characterization Of Soybean Accessionsmentioning
confidence: 99%
“…Two of the SSR markers amplifying unique alleles were known to be linked with two different phenotypic traits. The Satt055 was reported to be linked with photoinsensitivity trait (Liu et al 2011). The Satt055 had amplified a unique allele in accessions EC333915.…”
Section: Molecular Characterization Of Soybean Accessionsmentioning
confidence: 99%
“…The monthly mean air temperature from emergence to (Cober, 2011). Liu et al (2011) reported that in a tropical location, such as Thailand, planting starts in November because flowering time is affected by warmer temperature rather than by the photoperiod; therefore, the high temperature during the night has a more significant effect on the induction of flowering.…”
Section: Resultsmentioning
confidence: 99%
“…A flowering QTL in the Satt202-Satt371 (Chr 6) was for both Korea and China. The environmentally less sensitive QTL with higher phenotypic variation and maximum additive affect in China was shown than that in Korea (Liu et al, 2011). Different photoperiod and temperature on these two environments may contribute mainly for the distinctive flowering variations.…”
Section: A Case Study: Syntenic Qtl For Flowering At Different Latitudesmentioning
confidence: 88%
“…QTLs associated with complex abiotic and biotic stresses tolerance traits have been targeted and elucidated their relations with other traits by several approaches (www.phytozome.net/soybean; http://soybase.org). A number of QTLs for abiotic and biotic stresses as well as flowering/maturity have been identified using several populations across environments (Abdel-Haleem et al, 2012;Cheng et al, 2011;Hamwieh et al, 2011;Liu et al, 2011;Xing et al, 2012).…”
Section: Qtls For Tolerance To Abiotic and Biotic Stresses In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation